2013
DOI: 10.1111/gcbb.12062
|View full text |Cite
|
Sign up to set email alerts
|

Implications of land class and environmental factors on life cycle GHG emissions of Miscanthus as a bioenergy feedstock

Abstract: Replacement of fossil fuels with sustainably produced biomass crops for energy purposes has the potential to make progress in addressing climate change concerns, nonrenewable resource use, and energy security. The perennial grass Miscanthus is a dedicated energy crop candidate being field tested in Ontario, Canada, and elsewhere. Miscanthus could potentially be grown in areas of the province that differ substantially in terms of agricultural land class, environmental factors and current land use. These differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 36 publications
(57 reference statements)
1
21
0
Order By: Relevance
“…Upstream emissions (extraction of the natural gas in Alberta, processing and transport to the GS) and combustion at the GS are included in the analysis. We adapt models developed in prior studies (Zhang et al, 2010;Sanscartier et al, 2013) for this analysis. We do not consider retrofitting of the coal GS to natural gas boiler or NGCC systems in the present study.…”
Section: Reference Fossil Fuel Pathwaysmentioning
confidence: 99%
“…Upstream emissions (extraction of the natural gas in Alberta, processing and transport to the GS) and combustion at the GS are included in the analysis. We adapt models developed in prior studies (Zhang et al, 2010;Sanscartier et al, 2013) for this analysis. We do not consider retrofitting of the coal GS to natural gas boiler or NGCC systems in the present study.…”
Section: Reference Fossil Fuel Pathwaysmentioning
confidence: 99%
“…The land suitable for field crops is further classified into two subgroups: prime (classes 1, 2 and 3) and marginal land (classes 4 and 5). Agricultural land in the northern region is not suitable for Miscanthus (Miscanthus × giganteus) cultivation because of its short growing period (frost-free days are only 100-145 days) excluded from this study [17,31]. The area of land under different classes varies from region to region and scattered throughout the regions (Table S2).…”
Section: Study Areamentioning
confidence: 99%
“…Although all classes of cultivable lands are suitable for Miscanthus, yield, production cost, and net emission from cultivation are varied depending on the land classes, crop rotation, and regions [17,31]. Consequently, four scenarios have been established for various regions (Central, Southern, Western and Eastern Ontario) ( Table 1).…”
Section: System Boundary and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miscanthus also produced fewer GHG emissions than oil (Wang et al ., ). A study in Canada reported that in each of five electricity generation scenarios, M. × giganteus produced fewer life‐cycle emissions (g CO 2 eq k Wh −1 ) than coal (Sanscartier et al ., ). In addition, in scenarios of high productivity or/and soils currently poor in carbon, M. × giganteus would further reduce GHG emissions by soil C accumulation.…”
Section: Studies Dealing With the Environmental Effects Of Producing mentioning
confidence: 99%